Modelling Potential Fishing Zones of Mackerel Tuna (Euthynnus affinis) Using Sea Surface Temperature and Chlorophyll-a Derived from Satellite Remote Sensing in Fisheries Management Area 712, Java Sea, Indonesia - Muhammad Fadhil; Indah Raehana; Ema Pujiono (Journal of Marine Fisheries, 2026)
Mackerel tuna (Euthynnus affinis) is one of the economically important pelagic fish species in Indonesian waters. The distribution of this species is strongly influenced by oceanographic conditions, particularly sea surface temperature (SST) and chlorophyll-a concentration. This study aims to identify and model potential fishing zones (PFZs) of mackerel tuna in Fisheries Management Area (FMA) 712, Java Sea, using satellite-derived SST and chlorophyll-a data. Monthly SST and chlorophyll-a datasets obtained from MODIS Aqua were analyzed spatially and temporally. Fishing catch data were integrated with oceanographic variables to determine suitable habitat conditions for mackerel tuna. Geographic Information System (GIS) techniques and spatial overlay analysis were employed to generate PFZ maps. Results indicate that mackerel tuna catches were predominantly associated with SST ranging from 28–30°C and chlorophyll-a concentrations between 0.3–1.5 mg m⁻³. High potential fishing zones were concentrated in the northern and central parts of the Java Sea, particularly during the transitional and southeast monsoon seasons. The integration of SST and chlorophyll-a significantly improved the identification of productive fishing grounds. This study demonstrates the applicability of satellite remote sensing as an effective tool for supporting sustainable fisheries management and improving fishing efficiency in FMA 712.